Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1073/pnas.1009439108
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation impairs precision of waggle dance signaling in honey bees

Abstract: Sleep is essential for basic survival, and insufficient sleep leads to a variety of dysfunctions. In humans, one of the most profound consequences of sleep deprivation is imprecise or irrational communication, demonstrated by degradation in signaling as well as in receiving information. Communication in nonhuman animals may suffer analogous degradation of precision, perhaps with especially damaging consequences for social animals. However, society-specific consequences of sleep loss have rarely been explored, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 39 publications
(45 reference statements)
0
63
0
Order By: Relevance
“…Indeed, even when sleeping in flight, sleep was more fragmented and less deep than sleep on land. In contrast with frigatebirds, in animals ranging from insects [92] to humans [93], far shorter periods of sleep restriction and fragmentation [94] have profound adverse effects on their ability to maintain wakefulness and interact adaptively with the environment. People fall asleep while driving a car after losing just a few hours of sleep, even when aware of the dangers and trying to keep themselves awake.…”
Section: General Implicationsmentioning
confidence: 99%
“…Indeed, even when sleeping in flight, sleep was more fragmented and less deep than sleep on land. In contrast with frigatebirds, in animals ranging from insects [92] to humans [93], far shorter periods of sleep restriction and fragmentation [94] have profound adverse effects on their ability to maintain wakefulness and interact adaptively with the environment. People fall asleep while driving a car after losing just a few hours of sleep, even when aware of the dangers and trying to keep themselves awake.…”
Section: General Implicationsmentioning
confidence: 99%
“…5). However, several studies have suggested that honey bees do not compensate for sleep loss by increasing sleep duration; rather, they suggest that bees recover from sleep deprivation by intensifying their later sleep (Beyaert et al, 2012;Hussaini et al, 2009;Klein et al, 2010;Sauer et al, 2004). Moreover, even if young honey bees were compensating for sleep loss by increasing sleep duration, one would predict that 2 days of sleep deprivation will result in a greater sleep rebound than a single day of sleep deprivation, which is not consistent with our findings that sleep duration was similar for bees experiencing the colony environment for 1 or 2 days (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…From 3 weeks of adult life, honey bee workers typically forage for pollen and nectar outside the hive (Robinson, 1992;Winston, 1987). The sleep behavior of honey bees has been studied both in the natural context of the colony (Kaiser, 1988;Klein and Seeley, 2011;Klein et al, 2008;Klein et al, 2010) and in detailed laboratory studies (Eban-Rothschild and Bloch, 2008;Kaiser, 1988;Sauer et al, 2003). Honey bees exhibit all three behavioral characteristics of sleep: a period of quiescence (Eban-Rothschild and Bloch, 2008;Kaiser, 1988;Sauer et al, 2003;Sauer et al, 2004), an increased response threshold (Eban-Rothschild and Bloch, 2008; Kaiser, 1988;Kaiser and Steiner-Kaiser, 1983) and a homeostatic regulation mechanism (Klein et al, 2010;Sauer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only decoded waggle phases (the phase of the dance that contains location information) that occurred during 30-s intervals, with the start time of each interval separated by 5 min (starting from the beginning of our video footage). We determined the angles of the waggle phases with the aid of a MATLAB programme that we developed (inspired by a similar approach by Klein et al, 2010). A transparent MATLAB figure was overlaid on an external video player window (SMPlayer) and video was played back at slow speed (usually 1/4 speed).…”
Section: Apis Mellifera Swarm Dancesmentioning
confidence: 99%